Some practical suggestions for the scientific problem formulation and the objectives in the research project - Luis Alberto Corona Martínez; Mercedes Fonseca Hernández; Mercedes Corona Fonseca (Medisur)
One of the main difficulties for first-time researchers is writing the scientific problem and the objective of the research. The objective of this article is to provide an orientation on how to carry out the concrete moment of formulating the problem and, from this, how to write the objectives. Four variants are presented and exemplified for the writing of the research problem, from which corresponding concrete ways of formulating the objectives are derived. Emphasis is placed on inviolable requirements for the development of research objectives: full correspondence problem-objective, and the need to explicitly express the cognitive intent of the project.